Robot-assisted laparoscopic combined with endoscopic partial gastrectomy (RALE-PG) for the treatment of gastric gastrointestinal stromal tumors in challenging anatomical locations: single-center experience - Jian, Chenxing; Huang, Xinxiang; Lin, Ruirong; Yang, Weijin; Zheng, Shiyao; He, Hongxin; Jin, Shangkun; Yang, Chunkang; Guan, Shen (Frontiers in Surgery, 2024)
Background Gastric gastrointestinal stromal tumors in challenging anatomical locations are difficult to remove. Methods This study retrospectively analyzed the clinical data of 12 patients with gastric GISTs in challenging anatomical locations who underwent robot-assisted laparoscopic combined with endoscopic partial gastrectomy (RALE-PG) and manual suturing of the gastric wall. Results This study included 12 patients with a mean age of 56.8 ± 9.8 years and a mean BMI of 23.9 ± 1.9 kg/m2. Tumors were located in the GEJ (n = 3), lesser curvature (n = 3), posterior gastric wall (n = 3) and antrum (n = 3). The cardia and pylorus were successfully preserved in all patients regardless of the tumor location. The mean tumor size was 4.5 ± 1.4 cm. The mitotic-count/50 mm2 was less than 5 in all patients (100%). There was no intraoperative tumor rupture (0%) and no conversion to open surgery (0%). The median operation time was 122 (97–240) min, and the median blood loss volume was 10 (5–30) ml. The median postoperative VAS score was 2 (2–4). The median time to first flatus was 2 (2–3) days. The median time to first fluid intake was 2 (2–3) days. The median time to first ambulation after the operation was 3 (2–4) days. No cases of anastomotic stenosis or leakage were found. The median time to drain removal for 6 patients was 5 (4–7) days. The median time to nasogastric tube removal for all patients was 2 (1–5) days. The median postoperative hospital stay was 5 (4–8) days. One patient (female/41 year) developed moderate anemia (Clavien-Dindo grade II complication). There was no unplanned readmission within 30 days after the operation. The median distance from the tumor to the resection margin was 1 (1–2) cm. R0 resection was achieved in all patients. The median follow-up period was 19 (10–25) months, and all patients survived with no recurrence or metastasis. Conclusions RALE-PG is a safe, feasible and advantageous technique for treating GISTs in challenging anatomical locations. It can be used to accurately remove the tumor while preserving gastric function to the greatest extent, but long-term oncologic outcomes need to be evaluated in a study with a larger sample size and longer follow-up period.